Biainili-Urartu during the Reign of Ishpuini alone and together with his Son, Menua, according to the Research of K.F. Lehmann-Haupt - Sargsyan, Vahe (ՀՀ ԳԱԱ «Գիտություն» հրատ.)
Pioneer of Urartology, orientalist K.F. Lehmann-Haupt (1861–1938) during his research of the Armenian Highlands and Northern Mesopotamia (1898– 1899), among other ancient sites, also researched the probable region of Musasir, the religious center of the Kingdom of Van. Discussing the problems of the early period of the history of Van Kingdom (Urartu), the scientist considered as a special topic of a deep research the spread of the cult of the god Khaldi in the capital Tushpa and other areas out of the city. It is noteworthy, that in this context the researcher was the first to conduct a scientific discussion on the circumstances of the location of the bilingual inscription of Kelishin of Musasir region, its dates, about the scribe who recorded it, also the language of the inscriptions. According to K.F. Lehmann-Haupt, the city of Musasir was probably founded in the 9th century BCE and the cult of the god Khaldi was established there. The researcher believes that Menua’s brother, Sarduri was appointed viceroy in Musasir and there was a statue dedicated to him in the temple of Musasir the presence of which was evidenced in the description about the invasion of Urartu in 714 BCE by the Assyrian king Sargon II (721–705 BCE). Examining the road from Van to Musasir, K.F. Lehmann-Haupt considers it as a result of the Biainian engineering mind and notes that it was also built in accordance with the features of the transportation of the Biainian army. Կ.Ֆ. Լեման-Հաուպտը, Վանի թագավորությունում Իշպուինիի (մ.թ.ա. մոտ 830–820 թթ. միանձնյա և մ.թ.ա. 820–810 թթ. Մենուայի հետ համատեղ) գահակալության տարիների իրողությունները վերականգնելիս, առանցքային հետազոտական խնդիր էր դիտարկում բիայնական պետականության՝ դեպի Մուծածիր ծավալման և Խալդի աստծո պաշտամունքի ձևավորման ու զարգացման հանգամանքը: Ըստ այդմ, հեղինակն Իշպուինիի գահակալության տարիներին կատարված իրողությունների վերականգնման մեկնակետ է ընտրում Խալդի աստծո պաշտամունքի տարածումը Վանի թագավորությունում: Կ.Ֆ. Լեման-Հաուպտը, Վանա միջնաբերդի արևելյան կողմի իր ընթերցած արձանագրությունը (Թավրիզյան դարպասներ) հիմք ընդունելով, գտնում է, որ այս արձանագրությունը կազմվել է դեռևս Իշպուինիի միանձնյա գահակալության ժամանակաշրջանում և համաժանակյա է Մուծածիրի տաճարի կառուցմանը: Ուշագրավ է, որ Կ.Ֆ. Լեման-Հաուպտը դեռևս բիայնագիտության արշալույսին քննարկել է նաև բիայնացիների Մուծածիրից սերելու հանգամանքը և հնդեվրոպախոս շերտի առկայությունն այնտեղ: Կ.Ֆ. Լեման-Հաուպտը կարծում է, որ Մուծածիրի տաճարի կառուցվածքն աղերսվում է պոնտական-պաֆլագոնիական ոճին, որն էլ իր հերթին առնչվում է անտիկ տաճարների ճարտարապետությունը: Կ.Ֆ. Լեման-Հաուպտի հետազոտությունները Վանի թագավորությունում Խալդի աստծո պաշտամունքի տարածման վերաբերյալ ներկայումս նույնպես արդիական են՝ առնվազն պաշտամունքի տարածման և վերափոխման տարբեր փուլերի ծիրում: При воссоздании реалий Ванского царства в период правления Ишпуини (единолично – около 830–820 гг. до н.э., совместно с Менуа – 820–810 гг. до н.э. ), К.Ф. Леманн-Гаупт главной исследовательской проблемой Урартской государственности считал расширение территорий в направлени Мусасира, а также особенности формирования и развития культа бога Халди. Соответственно, воссоздавая историческую картину периода правления Ишпуини, в качестве исходной точки автор рассматривает распространение культа бога Халди в Ванском царстве. К.Ф. Леманн-Гаупт, основываясь на надписи на восточной стороне Ванской цитадели (Тебризские ворота), приходит к выводу, что данная надпись относится к периоду единоличного правления Ишпуини и строительства храма в Мусасире. Примечательно, что К.Ф. Леманн-Гаупт, ещё на начальной стадии изучения урартологии, выдвинул точку зрения о происхождении биайнийцев из Мусасира и наличии там говорящей на индоевропейском языке прослойки. По мнению К.Ф. Леманн-Гаупта, архитектурный стиль храма Мусасира перекликается с понтийско-пафлагонским стилем, характерным для древних храмов. Исследования К.Ф. Леманн-Гаупта, посвященные распространению культа бога Халди в Ванском царстве, актуальны по сей день, по крайней мере, в плане распространения и трансформации культа на разных этапах.
Keywords: History